Construction of multicomponent nanocomposite CdSe/NaYF4:Yb, Er colloidal spheres for tuning visible light. (August 2019) - Liu, Lihua; Jiao, Jiqing; Wei, Wei; Lv, Baize; Liu, Yi; Hu, Zhongyi; Tang, Jianguo
Abstract: Multicomponent nanocomposite colloidal spheres were synthesized with NaYF4 :Yb, Er upconversion nanoparticle and CdSe quantum dots for tailoring visible emission. The CdSe/NaYF4 :Yb, Er colloidal spheres were synthesized by improved emulsion-based self-assembly approach. They are well-dispersed in the colloidal sphere by electron diffraction X-ray mapping patterns. The colloidal spheres exhibited near-infrared photoresponse property. The intensity of short-wavelength emission at 408 nm was drastically weakened, and a red emission at 655 nm is substantially increased. Both the mechanism and multi-photon process of upconversion photoresponse was determined. It offers facile strategy to assemble multicomponent nanocomposite colloidal spheres for tuning visible emission. Graphical abstract: The multicomponent nanocomposite CdSe/NaYF4 :Yb, Er colloidal spheres were constructed and its visible emission was tuned under near-infrared excitation.Unlabelled Image